2010
DOI: 10.1021/ja103327f
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Diversity in Nanoscale Electrical Break Junctions

Abstract: The realization of molecular-scale electronic devices will require the development of novel strategies for controlling electrical properties of metal/molecule/metal junctions, down to the single molecule level. Here, we show that it is possible to exert chemical control over the formation of metal/molecule...molecule/metal junctions in which the molecules interact by pi-stacking. The tip of an STM is used to form one contact, and the substrate the other; the molecules are conjugated oligophenyleneethynylenes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
145
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(164 citation statements)
references
References 53 publications
18
145
1
Order By: Relevance
“…This is an important consideration as for certain classes of -conjugated molecules, for instance oligo(phenylene)ethynylene (OPE) derivatives, it has been shown that proximal molecular bridges can -stack in molecular electrical junctions and can, on occasions, give rise to additional complications in the conductance signatures of such compounds. 20,46 11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important consideration as for certain classes of -conjugated molecules, for instance oligo(phenylene)ethynylene (OPE) derivatives, it has been shown that proximal molecular bridges can -stack in molecular electrical junctions and can, on occasions, give rise to additional complications in the conductance signatures of such compounds. 20,46 11…”
Section: Resultsmentioning
confidence: 99%
“…19 More direct assessment of the electrical properties of oligoynes can be achieved by wiring them into electrical junctions with metal contacts. 4,20 Here we report conductance measurements of novel molecular wires Me 3 Si-(C≡C) n -SiMe 3 (n = 2, 3, 4, 5; Scheme 1), using STM-based techniques. In particular the influence of the solvent on conductance and -values has been investigated, and complemented by DFT computations of charge transport through the molecular bridge.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the Authiol bond is initially near a step edge on the gold nanoparticle, it may jump over this edge to the upper gold layer upon pulling. Recently, Martin et al argued that the latter configuration yields a higher resistance value [19]. 4 We anticipate, however, that the situation will be very different for less rigid molecules.…”
Section: Showing (R( D) − R(0))/r(0) Versus Y and Semilogarithmicallmentioning
confidence: 86%
“…Polycrystalline gold and platinum disc electrodes with the diameter of 1.6 mm and 2.0 mm, respectively, were used for the preparation of self-assembled monolayers. Thioacetates 2 [58] and 3 [60] were synthesized as reported previously.…”
Section: Methodsmentioning
confidence: 99%